Perspectives of Hydrogen Fuel Cells in Aviation - Mamadjanov Lochinbek Yusupovich, (Zien Journals, 2022)
This article deals with perspectives of hydrogen fuel cells in aviation sphere. It should be noted that Hydrogen fuel cells are emerging as a high-potential technology that offers significant energy efficiency and decarbonisation benefits to a range of industries – including automotive and heavy transport. This paper presents and discusses the classification, working principles, characteristics, and critical technologies of hydrogen fuel cells. Additionally, future technologies and development, including the high-power density motors, converters, power supplies, are discussed for the hydrogen fuel cells in aviation industry.
Keywords: hydrogen fuel; potential technology; aviation industry; converter